Regular cold-water immersion following HIIT does not affect intramuscular adaptation markers, inflammatory profile or endurance performance - Malta, E. S.; Rosa Neto, J. C.; Beck, W. R.; Cornachione, A. S.; de Poli, R. A. B.; Sigoli, E.; Zagatto, A. M. (Scandinavian Journal of Medicine & Science in Sports, 2026)
The study aimed to investigate the effects of 5 weeks of post-exercise cold-water immersion (CWI) following high-intensity interval training (HIIT) sessions on the satellite cell pool, muscle content of inflammatory markers, muscle expression of peroxisome proliferator-activated receptor-y coactivator 1-a (PGC-1a), maximal oxygen uptake (VO2max), and running performance. Sixteen healthy males completed baseline assessments, including muscle biopsies, a graded exercise test for VO2max determination, and a constant work-rate (CWR) running test to assess time to task failure (TTF). Participants were ranked according to VO2max and randomly allocated to either a training-only control group (n = 7) or a CWI group (n = 9), which underwent CWI (11.2°C ± 0.2°C for 15 min) following each HIIT session. The HIIT program consisted of three weekly sessions 5-8 × 2-min bouts at 95% VO2max. At the end of weeks four and five, all participants repeated the same sequence of assessments. Training increased VO2max values, TTF at CWR, satellite cell pool, PGC-1a content, and induced changes in muscle morphology (connective tissue), as indicated by a main effect of time (p = 0.031); none of the analyzed variables showed a main effect of condition (p = 0.098) or interaction (p = 0.088). No significant alterations were observed in inflammatory markers over time (p = 0.395) and condition (p = 0.115). In conclusion, 5 weeks of post-exercise CWI following HIIT did not influence the satellite cell pool, muscle inflammation status, muscle PGC-1a content, muscle morphological, VO2max, or running performance.